REALIZATION OF THE CONCEPT OF “CONSCIENCE” IN PROVERBS - Nurullayeva Madina Rashidjon qizi; Khayrieva Madina Ilhomovna (Лучшие интеллектуальные исследования, 2024)
Annotation: This article delves into the multifaceted concept of conscience, exploring various philosophical interpretations and cultural perceptions throughout history. It begins by highlighting the challenge of defining conscience, noting its diverse interpretations across different cultures and philosophical frameworks. Proverbs are presented as a means of elucidating the concrete and certain nature of conscience, often portraying it as an internal oracle that guides human behavior.